Textual Analysis of Chilean Early Childhood Educators' Perception of the Curricular Bases - Concha-Díaz, Valeska (2022)
This study aims to analyze the contributions and perceptions of a group of early childhood educators regarding the updating of the Curricular Bases for Kindergarten Education in Chile. Based on the frequency analysis, and supported by statistical programs, the author grouped the words employed by the participants according to their meaning (semantic grouping). Thus, groups of words referring to the use of the document in their pedagogical work were formed. To achieve the above, the investigator chose a graphical approach that allowed representing a two-dimensional space of the groups of words in which the surveyed group and the respective analyzes were considered. The results revealed that the textual analysis contributed to a deeper understanding of this previously unaddressed topic, which, at the same time, holds implications for the educational practice of the participating group, since there exist significant differences between the responses of nursery school educators according to the type of dependency in which they work.